(untitled) (Indonesian Journal of Agrarian Law, 2026)
The issuance of land title certificates must be carried out in accordance with the principle of prudence to ensure legal certainty and protection for the community. However, in practice, there are still instances where Certificates of Right to Build (SHGB) are issued for cultivated land that has been physically controlled by the community for decades, thereby giving rise to land disputes. This study aims to analyze the implementation of the principle of prudence in the issuance of SHGBs by the ATR/BPN Land Office of Bogor Regency and to analyze the form of legal liability for the issuance of SHGBs on cultivated land that has been under community control for more than 20 years. This study employs a legal-empirical method using a statutory approach, a case study approach, and a conceptual approach. The results of the study indicate that the issuance of SHGB No. 4817/Sukahati in the name of PT. Star Tjemerlang administratively meets formal requirements; however, substantively, it does not align with the physical control of the land, which has been under Marja’s control since 1987. The discrepancy between physical and legal data indicates that the principle of due diligence has not been optimally applied, particularly in field verification and land history research. This study contributes to strengthening the concept of the Land Office’s legal accountability through the approach of unlawful acts by the government (onrechtmatige overheidsdaad).